Predictive Modeling of CSH Formation in Cement Materials Based on SEM and EDS Analysis - Beskopylny, Alexey N.; Hematibahar, Mohammad; Kharun, Makhmud; Stel'makh, Sergei A.; Shcherban', Evgenii M.; Ananova, Oxana (Civil Engineering Journal, 2025)
Calcium silicate hydrate (CSH) formation is a fundamental process required to enhance the density, strength, and durability of cementitious materials. However, there is a gap in the research on the structural, physical, and chemical transformations of CSH. The objectives of this study are to develop a predictive model of CSH formation in cementitious materials and evaluate the effects of gelatin powder (GP), silica fume (MS), ground coffee (SCG), and peanut shell (PS) on CSH formation. Scanning Electron Microscopy (SEM) and Energy Dispersive X-Ray Spectroscopy (EDS) apply to the study of the composite cementitious materials. A multiple linear regression model is proposed to predict the changes of key elements, which improved the qualitative and quantitative understanding of the hydration mechanisms. The results show that GP significantly accelerates CSH formation by increasing the calcium and oxygen contents, while MS enhances pozzolanic activity by increasing the availability of silicon, resulting in structural densification. SCG contributes to the increase of carbon and oxygen by acting as a filler, while PS has minimal effect on hydration or crystallization. A regression model relating cement mix design proportions and CSH shows strong correlations between admixtures and chemical changes, particularly for calcium (R²=0.988) and silica (R²=0.985). To fill the existing research gaps, this study goes beyond previous studies, which primarily focused on individual aspects of CSH formation without considering the convergence of structural and chemical analysis.